Teaching resources aimed at teaching science to students with visual impairments in a municipality in the semi-arid region of Piauí (Research, Society and Development, 2022)
The attendance to students with visual impairment has become a reality in many municipalities in Brazil, through the creation of support policies and assurance of attendance the multiple deficiencies. With this scenario, the work proposes to present the didactic resources produced and used by teachers at the public school system in the municipality of Picos, located in the semi-arid region of Piauí, aimed at learning Science with students with visual impairments in Educational Service rooms. It opted for descriptive research of qualitative approach that it has as subjects teachers who work with specialized educational care (ESA). For data collection, school visits were held to offer the AEE to identify the materials available and interview teachers. The analysis of the data occurred interpretively in reading times allowing the identification of the subjects and interpretation of the data in categories of analysis, consisting that the machine and printer in Braille, in addition to the “reglete”, puncture, and magnifying glass are the materials available in the aforementioned public school for work with students with visual impairment and science teaching, not being identified teaching materials for this purpose and that more investments are needed for the educational care of the students with disabilities visual in the public education network.